Megasporogenesis and embryogenesis in three sympatric Posidonia seagrass species - Ma, G.; Zhang, X.; Bunn, E.; Dixon, Kingsley (2012)
Microsporogenesis, megasporogenesis and embryogenesis were studied using Posidonia australis as representative among three sympatric species in the seagrass genus Posidonia (P. australis, P. coriacea and P. sinuosa). Each flower spikelet has only one ovary (this is common to the three species). With P. australis the microspore is initially globular then becomes baton-like and finally matures into stick- or thread-like pollen. The mature embryo sac is four-nucleate comprising one polar nucleus, one egg cell and two syngerids, however as the embryo sac becomes mature, only three nucleate cells dominate, comprising one central cell (polar nucleus), one egg cell and one syngerid. After fertilization, the fertilized cell divides into two longitudinally. The basal cell ceases division, vacuolates and may function as a conduit for nutrients to the upper, dividing cell(s). The upper cell firstly divides transversely into two cells and then longitudinally into four cells that in turn develops into a globular zygotic embryo attached by the basal cell. The globular zygotic embryo morphs into a shuttle-shaped embryo and loses attachment to the basal cell. This developmental sequence also appears to apply to P. coriacea and P. sinuosa.